Proceedings of the 2002 ACM Conference on Computer Supported Cooperative Work 2002
DOI: 10.1145/587078.587102
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for photoware

Abstract: Eleven PC-owning families were interviewed at home about their use of conventional and digital photos. They also completed photo diaries and recorded photo-sharing conversations that occurred spontaneously over a three month period after the in-home interviews. From an analysis of the resulting materials we illustrate the strengths and weaknesses of past and present technology for photo sharing. These allow us to prioritise user requirements for a range of future photo-sharing technologies or 'photoware'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(165 citation statements)
references
References 9 publications
9
153
0
3
Order By: Relevance
“…Van House et al, 2005). Other gratifications of online photo sharing, such as feedback, public approval, attention, recognition, and social rewards in yje form of comments and consequent conversation on shared photos, have also been 5 frequently highlighted in the literature (Ames & Naaman, 2007;Frohlich et al, 2002;Malinen, 2011;Nov et al, 2010). Many people engage in the activity out of habit, as they wish to share and get appreciation and attention from a wider audience on the web rather than just family members (Frohlich, Robinson, Eglinton, Jones, & Vartiainen, 2012;Miller & Edwards, 2007).…”
Section: Digital Photo Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Van House et al, 2005). Other gratifications of online photo sharing, such as feedback, public approval, attention, recognition, and social rewards in yje form of comments and consequent conversation on shared photos, have also been 5 frequently highlighted in the literature (Ames & Naaman, 2007;Frohlich et al, 2002;Malinen, 2011;Nov et al, 2010). Many people engage in the activity out of habit, as they wish to share and get appreciation and attention from a wider audience on the web rather than just family members (Frohlich, Robinson, Eglinton, Jones, & Vartiainen, 2012;Miller & Edwards, 2007).…”
Section: Digital Photo Sharingmentioning
confidence: 99%
“…Sharing photos online can help people in fulfilling their social interaction needs, such as selfexpression, self-presentation, communicating, and maintaining and nurturing social relationships (Frohlich, Kuchinsky, Pering, Don, & Ariss, 2002;Goh et al, 2009;Oeldorf-Hirsch & Sundar, 2010;Pering, Nguyen, Light, & Want, 2005;N. Van House et al, 2005).…”
Section: Digital Photo Sharingmentioning
confidence: 99%
“…Frohlich et al (2008) identified collaborative photo-work by observing the emergence of photo-talk during photo-work activities. The different nature of talk contents has already been identified in (Frohlich et al 2002), in particular with regard to storytelling and reminiscing.…”
Section: Home Vs Professional Usage Of Photographsmentioning
confidence: 94%
“…In the CSCW literature, the practices surrounding the management of photographs have been observed and studied mainly in the home where they are the objects of individual and collaborative activities (Frohlich et al 2002;Crabtree et al 2004;Kirk et al 2006). On the one hand, these activities are aimed at building a record of meaningful events, people, and places, while on the other hand at retrieving this record and sharing it with relatives and friends both in co-located and distributed settings.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nardi et al's study found that people use blogging Web sites for posting text and pictures to document their lives and those of their children, which in turn can maintain and strengthen social ties with people living away [21]. Similarly, while studying photo-sharing practices in the UK, Frohlich et al [22] found that parents use photos to enhance phone conversations among distant relatives and to provide the means to keep them aware of the children's development. These studies highlight the importance of picture sharing for enhancing connectedness, but also the relevance of photo storytelling is investigated in this paper.…”
Section: Young Mothers Internet and Photo-sharing Practicesmentioning
confidence: 99%